2009
DOI: 10.1097/pcc.0b013e31819a383c
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the pharmaceutical excipients benzyl alcohol and propylene glycol among critically ill neonates

Abstract: Critically ill neonates, especially those receiving medications by continuous infusion, are at risk of being exposed to BA and PG at potentially toxic doses during routine medication administration. Given the serious adverse reactions known to be associated with BA and PG, future studies are warranted to determine the clinical consequences associated with this degree of excipient exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 14 publications
4
60
0
1
Order By: Relevance
“…ESAs and iron can be continued. Preservative-free heparin should be used as the additive benzyl alcohol can be toxic to preterm infants [47]. Emotional support is also essential: many new mothers can no longer manage home-based dialysis and need to temporarily transition to in-center therapy.…”
Section: Management Of the Pregnant Patient On Hemodialysismentioning
confidence: 99%
“…ESAs and iron can be continued. Preservative-free heparin should be used as the additive benzyl alcohol can be toxic to preterm infants [47]. Emotional support is also essential: many new mothers can no longer manage home-based dialysis and need to temporarily transition to in-center therapy.…”
Section: Management Of the Pregnant Patient On Hemodialysismentioning
confidence: 99%
“…61 A number of recent studies in NICUs revealed systemic concentrations of excipients that were intolerable even in older age groups. 54,62,63 The urgent need to understand these safety concerns has led to a collaborative effort by the United States and the European Union to create a STEP (Safety and Toxicity of Excipients for Pediatrics) database. Its aim is to improve systematic data collection on excipient toxicity and tolerance in children.…”
Section: Potential Limitations Of Pediatric Drug Formulationsmentioning
confidence: 99%
“…Excipients have been associated with adverse effects and large amounts can be administered to hospitalized neonates [68][69][70] and are difficult to study [71]. The neonatal administration of propylene glycol [72] and benzyl alcohol [31] in injectable drug formulations has been associated with serious adverse effects, including death.…”
Section: Excretionmentioning
confidence: 99%